Dampak Pandemi Covid-19 pada Operasional Hotel di The Atrium Hotel and Resort Yogyakarta - Eko Yuli Sutrisno; Fitroh Adhila (Media Wisata, 2021)
The purpose of this article is to analyze the impact of the COVID-19 pandemic on hotel operation at The Atrium Hotel and Resort Yogyakarta. This study is using a descriptive qualitative approach. The results of the study indicate operational constraints faced by The Atrium Hotel and Resort during the COVID-19 pandemic, which include a longer check-in process, increased operational cost, food and beverage services are not optimal, difficulties in determining the selling price of rooms, difficulty finding guests, and difficulty arranging the employee work schedules. The effort to adjust The Atrium Hotel and Resort Yogyakarta’s operation amid the COVID-19 pandemic are modifying of standard operating procedure (SOP), selling room only, adding facilities to prevent the spread of COVID-19, strict monitoring of health protocols, and MICE activities requiring permission from the COVID-19 force